The association between SARS‐CoV‐2 infection and late pregnancy loss. Issue 1 (22nd November 2021) - Ganor Paz, Yael; Shiloh, Sivan; Brosh‐Nissimov, Tal; Grupel, Daniel; Sorek, Nadav; Kustin, Talia; Stern, Adi; Maklakovsky, Marina; Polak, Mia; Sharvit, Merav; Neeman, Ortal; Ben Valid, Tal; et al.
Abstract : SARS‐CoV‐2 vertical transmission with confirmed placental infection, confirmed by whole genome sequencing of the virus, may be a contributing factor to fetal demise.